2015
DOI: 10.1371/journal.pone.0139221
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 5-Aza-2'-Deoxycytidine Induces Expression of NY-ESO-1 and Facilitates Cytotoxic T Lymphocyte-Mediated Tumor Cell Killing

Abstract: BackgroundNY-ESO-1 belongs to the cancer/testis antigen (CTA) family and represents an attractive target for cancer immunotherapy. Its expression is induced in a variety of solid tumors via DNA demethylation of the promoter of CpG islands. However, NY-ESO-1 expression is usually very low or absent in some tumors such as breast cancer or multiple myeloma. Therefore, we established an optimized in vitro treatment protocol for up-regulation of NY-ESO-1 expression by tumor cells using the hypomethylating agent 5-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…This compound inhibits DNA methyltransferase leading to a reduction in DNA methylation [38]. We observed that Fn14 expression was up-regulated after 5-aza-dC treatment, but the effect was not strictly dose-dependent, consistent with a previous report examining 5-aza-dC activity on antigen presentation in breast cancer cells [48]. Our results suggest that the low level of Fn14 protein expression noted in both IDH1 mutant-overexpressing cells and IDH1 mutant tumors may be due, at least in part, to transcriptional repression by an epigenetic mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…This compound inhibits DNA methyltransferase leading to a reduction in DNA methylation [38]. We observed that Fn14 expression was up-regulated after 5-aza-dC treatment, but the effect was not strictly dose-dependent, consistent with a previous report examining 5-aza-dC activity on antigen presentation in breast cancer cells [48]. Our results suggest that the low level of Fn14 protein expression noted in both IDH1 mutant-overexpressing cells and IDH1 mutant tumors may be due, at least in part, to transcriptional repression by an epigenetic mechanism.…”
Section: Discussionsupporting
confidence: 90%
“…Such differences might be caused by different promoter regions or tissues selected or variability in test methods. 5-Aza-CdR is a methyltransferase inhibitor that can restore gene expression by demethylation (Klar et al, 2015). A previous study found restoration of E-Cadherin expression in a prostate cancer cell line after treatment with 5-Aza-CdR (Li et al, 2001), further suggesting the regulation of E-Cadherin expression by promoter methylation.…”
Section: Introductionmentioning
confidence: 94%
“…31 They function as DNA methyltransferase inhibitors (DNMTis), causing hypomethylation of DNA. Treatment of tumor cells with DNMTis can re-activate hypermethylated tumor suppressor genes, increase tumor cell immunogenicity by re-activating cancer testis and differentiation antigens, [32][33][34][35][36] and increase antigen presentation and MHC class I expression. 37 Recent studies suggest that DNMTis can induce a sustained interferon response in cancer cells by activating retroviral encoded double-stranded RNA.…”
Section: Introductionmentioning
confidence: 99%